Yin Yang 1 Promotes Hepatic Gluconeogenesis Through Upregulation of Glucocorticoid Receptor - Lu, Yan (American Diabetes Association, 2013)
Gluconeogenesis is critical in maintaining blood glucose levels in a normal range during fasting. In this study, we investigated the role of Yin Yang 1 (YY1), a key transcription factor involved in cell proliferation and differentiation, in the regulation of hepatic gluconeogenesis. Our data showed that hepatic YY1 expression levels were induced in mice during fasting conditions and in a state of insulin resistance. Overexpression of YY1 in livers augmented gluconeogenesis, raising fasting blood glucose levels in C57BL/6 mice, whereas liver-specific ablation of YY1 using adenoviral shRNA ameliorated hyperglycemia in wild-type and diabetic db/db mice. At the molecular level, we further demonstrated that the major mechanism of YY1 in the regulation of hepatic glucose production is to modulate the expression of glucocorticoid receptor. Therefore, our study uncovered for the first time that YY1 participates in the regulation of hepatic gluconeogenesis, which implies that YY1 might serve as a potential therapeutic target for hyperglycemia in diabetes.